1991
DOI: 10.1017/s0317167100032194
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Joint Reaching Movements and Eye-Hand Tracking in Cerebellar Incoordination: Investigation of a Patient with Complete Loss of Purkinje Cells

Abstract: Performance on an eye-hand tracking task and a multi-joint reaching movement to a visual target was studied in a patient with stable cerebellar ataxia and in control subjects. The patient subsequently died and a full neuropathological examination was performed. The neuropathological findings were similar to those seen in patients with paraneoplastic cerebellar degeneration, but no tumor was found at autopsy eight years after onset of the patient's cerebellar syndrome. A severe cerebellar cortical degeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Similarly, for arm movements, Holmes (1922) described disorders and variability in their direction, range and rate. In agreement, recent studies of multijoint arm movements in cerebellar patients have found increased trial-to-trial variability in hand trajectories in throwing (Becker et al 1990;Timmann et al 1999Timmann et al , 2000 in reaching (Becker et al 1991;Day et al 1998), and in a pointing task (Bastian et al 1996) and increased variability in the timing of finger opening in throwing (Timmann et al 1999(Timmann et al , 2000.…”
Section: Increased Variability Is Associated With Lack Of Skill and Wsupporting
confidence: 65%
“…Similarly, for arm movements, Holmes (1922) described disorders and variability in their direction, range and rate. In agreement, recent studies of multijoint arm movements in cerebellar patients have found increased trial-to-trial variability in hand trajectories in throwing (Becker et al 1990;Timmann et al 1999Timmann et al , 2000 in reaching (Becker et al 1991;Day et al 1998), and in a pointing task (Bastian et al 1996) and increased variability in the timing of finger opening in throwing (Timmann et al 1999(Timmann et al , 2000.…”
Section: Increased Variability Is Associated With Lack Of Skill and Wsupporting
confidence: 65%
“…Frequently mentioned are slight visuo-manual tracking delays, errors of direction, velocity, acceleration and deceleration, and of timing of muscle contraction. 510 Presumed to be present in simple movements, these various errors are proposed to combine to cause the relatively greater errors seen in the compound movements (cf Becker et al 6 ). This position would seem to have been supported by the finding in laboratory animals of cerebellar neural discharge that leads movement onset and that correlates with the direction, position, velocity, and force of movement, as if it played a direct role in controlling these parameters of movement."…”
Section: Can J Neurol Sci 1993; 20 (Suppl 3): S93-s104mentioning
confidence: 99%
“…Humans with cerebellar pathology demonstrate poor performance in measures of speed or velocity perception (Ivry and Diener, 1991;Grill et al, 1994), hand-target mismatch in oculomanual tracking (van Donkelaar and Lee, 1994), and inconsistent specification of movement direction (Becker et al, 1991). Lesion and inactivation experiments in animals support these observations, finding decreased coordination of ocular and manual motor systems (Vercher and Gauthier, 1988) and increased error during hand tracking (Miall et al, 1987).…”
mentioning
confidence: 94%